Strategi Pembelajaran Keterampilan Menulis Untuk Kelas 4 Sekolah Dasar - Juliati Juliati; Nasya Aulia Andini; Ainun Rohma Siregar; Khairiana Suci Cahaya; Dini Azura; Nurul Hasanah (Journal of Innovative and Creativity, 2026)
Writing skill learning in elementary schools plays an essential role in developing students’ critical, creative, and communicative abilities. At the fourth-grade level, writing instruction should be systematic and meaningful to help students express ideas clearly and coherently. This article discusses five effective strategies for enhancing writing skills: the Process Writing Approach, Project-Based Learning, Cooperative Learning, Contextual Teaching and Learning, and Mind Mapping using visual media. These strategies guide students through gradual writing processes, connect learning with real experiences, and foster motivation and confidence. Within the Merdeka Curriculum framework, teachers act as facilitators who lead students through active and reflective writing activities. Appropriate implementation of these strategies transforms writing into a medium for literacy growth and character development in elementary students.